2004
DOI: 10.1007/s00125-003-1264-8
|View full text |Cite
|
Sign up to set email alerts
|

The vasopeptidase inhibitor AVE7688 ameliorates Type 2 diabetic nephropathy

Abstract: Aim/hypothesis. Pharmacological inhibition of the renin angiotensin system has proven clinical efficacy in nephropathies of various origins, including diabetic nephropathy. We tested the effects of the dual inhibition of both angiotensin converting enzyme and neutral endopeptidase by the vasopeptidase inhibitor AVE7688 in an animal model of Type 2 diabetic nephropathy. Methods. We treated 56 obese Zucker diabetic fatty (ZDF, Gmi-fa/fa) rats aged 34-weeks with either placebo (n=9) or the vasopeptidase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…We have previously shown that chronic vasopeptidase inhibition by AVE7688 prevents diabetic nephropathy in ZDF rats [19,22]. The present study demonstrates that AVE7688 also prevents accumulation of the AGEs CML, pentosidine and 3-DG-imidazolone in the diabetic kidney, which offers a mechanistic explanation for the profound nephroprotective effects of vasopeptidase inhibition in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have previously shown that chronic vasopeptidase inhibition by AVE7688 prevents diabetic nephropathy in ZDF rats [19,22]. The present study demonstrates that AVE7688 also prevents accumulation of the AGEs CML, pentosidine and 3-DG-imidazolone in the diabetic kidney, which offers a mechanistic explanation for the profound nephroprotective effects of vasopeptidase inhibition in the diabetic kidney.…”
Section: Discussionsupporting
confidence: 66%
“…benzapin-4-carboxy-acid, and its molecular weight is 432.5 g/mol [22]. AVE8048 is the active thiol form of AVE7688.…”
Section: Evaluation Of Chelating Activity Of Ace and Vasopeptidase Inmentioning
confidence: 99%
“…The nephropathy in this model has been described as focal segmental glomerulosclerosis associated with glomerulomegaly and mesangial expansion [14,15]. Previous studies have shown that the development of diabetic nephropathy in obese ZDF rats can be ameliorated by treatment with peroxisome proliferator-activated receptor-gamma agonists [16,17], ACE inhibitors and angiotensin II receptor blockers (ARBs) [18,19], vasopeptidase inhibitors [19,20], antivascular endothelial growth factor antibodies [21] and antioxidants [15]. These intervention studies strongly suggest that the pathogenesis of renal damage in type 2 diabetes involves a complex interrelationship of metabolic and/or haemodynamic factors.…”
mentioning
confidence: 99%
“…Accordingly, the aim of our study was to investigate involvement of the RAAS and/or the natriuretic peptide system in the pathophysiology of progressive renal damage after MI. We investigated the renoprotective effects of ACEi with lisinopril versus combined ACE/NEP inhibition with the vasopeptidase inhibitor AVE7688 (21)(22)(23).…”
mentioning
confidence: 99%